2016
DOI: 10.1111/bcpt.12663
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory Effect of Erythropoietin in the TNBS‐induced Colitis

Abstract: Erythropoietin is a potent stimulator of erythroid progenitor cells, which is able to inhibit NF-kB activation, due to its pleiotropic properties, thus promoting an anti-inflammatory effect. As inflammatory bowel disease is a chronic disease with reduced quality of life, and the current pharmacotherapy only induces or maintains the patient in remission, there is a crucial need of new pharmacological approaches. The main objective of this study was to evaluate the effect of erythropoietin in the TNBS-induced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 42 publications
11
34
0
Order By: Relevance
“…Therefore, in this study, we used macrophages instead of primary endometrial epithelial cells to explore the underlying mechanism of PD, which could have more general applicability—that is, PD may also play a similar role in other inflammatory diseases that have been confirmed in our previous studies . In this research, we evaluated the protective effects of PD in vivo using histological analyses, including H&E, immunofluorescence staining of phosphorylated NF‐κB involved in the regulation of the inflammatory process and the TUNEL assay as well as some of the crucial apoptosis‐related proteins. All of the in vivo experiments showed that PD can ameliorate the pathological conditions and attenuate the phosphorylation of NF‐κB and anti‐apoptotic effect, indicating that PD may have potential anti‐inflammatory and anti‐apoptotic effects in LTA‐induced injury in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, we used macrophages instead of primary endometrial epithelial cells to explore the underlying mechanism of PD, which could have more general applicability—that is, PD may also play a similar role in other inflammatory diseases that have been confirmed in our previous studies . In this research, we evaluated the protective effects of PD in vivo using histological analyses, including H&E, immunofluorescence staining of phosphorylated NF‐κB involved in the regulation of the inflammatory process and the TUNEL assay as well as some of the crucial apoptosis‐related proteins. All of the in vivo experiments showed that PD can ameliorate the pathological conditions and attenuate the phosphorylation of NF‐κB and anti‐apoptotic effect, indicating that PD may have potential anti‐inflammatory and anti‐apoptotic effects in LTA‐induced injury in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…TNBS was instilled as an intracolonic single dose as previously described by Mateus et al [13]. Briefly, mice were left unfed during 24 h. In the induction day (day 0), mice were anesthetized with ketamine 100 mg/kg + xylazine 10 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Shin and Cho suggested a novel strategy of EPO and granulocyte colony-stimulating factor combination therapy for stroke patients in their exploratory study. [2] In addition, EPO had a neuroprotective role in rotenoneinduced parkinsonism in rats, [3] an anti-inflammatory effect in the development of experimental colitis, [4] and a role in the regulation of body weight, fat mass, and glucose metabolism. [5] On the other hand, there is an increased mortality rate with recombinant human EPO treatment in stroke patients due to the toxicity of the high dose of EPO, this toxicity may partially result from increased hematocrit (Hct)-associated side effects, such as hypertension and thromboembolism.…”
Section: Introductionmentioning
confidence: 99%